Total synthesis of the putative structure of the proposed Banyasin A - Gao, Xuguang; Ren, Qi; Choi, Sun; Xu, Zhengshuang; Ye, Tao (Frontiers in Chemistry, 2015)
The first total synthesis of four possible isomers of a molecule possessing the stereochemistry proposed for banyasin A is described. The structure synthesized appears to be different from that of the natural product.